Experimental quantification of punching shear capacity for large-scale GFRP-reinforced flat slabs made of synthetic fiber-reinforced self-compacting concrete dataset - Mohammad AlHamaydeh (Data in Brief, 2021)
This article provides experimental data on the punching shear behavior of synthetic fiber-reinforced slabs reinforced with glass fiber reinforced polymer (GFRP) bars and cast from self-consolidating concrete (SCC). The data was collected from tests performed on six full-scale specimens centrically loaded until failure as indicated by penetration of the column stub into the slab and achieving a sharp drop in the load carrying capacity. Three different reinforcement bar spacings were used to consider the effect of reinforcement ratio on punching shear resistance. Three of the specimens tested were reinforced by 1.25% of volume of synthetic fiber, and three were control specimens cast from regular SCC. Applied load, central deflections, and bar strain were monitored during the experiment and are provided in the supplementary data. Any future models for analyzing the punching shear behavior and capacity of flat slabs reinforced with GFRP rebars will find this data valuable for model validation, and for establishing suitable safety factors for design. Numerical studies on the simulation of fiber-reinforced concrete would also find value in this data to validate the numerical model and enable it to be used for further studies.